Blog-Based Writing Instruction in Fostering EFL Writing Performance: Students’ Belief and Attitudes - St Hartina; Nurhasanah Safei; Nur Tahan Riani (Journal of Education Technology, 2023)
The existence of blogs offers an innovation that encourages a new writing style integrated with technology. However, it seems that there are still not many EFL writing classes in Indonesia using online blogs, and little research has been conducted on how students’ perception of a blog in writing. This study aims to analyze the Indonesian EFL learners' perceptions toward the use of Blog as the medium of learning practices in English Writing class. This study use qualitative research involving a questionnaire and semi-structured interviews were used. For 12 weeks, thirty-four students participated in this study by posting weekly entries from their English writing assignments on blogs. The data from the questionnaire reveals that the majority of students strongly agree and agree with the usefulness, effectiveness, attitudes, and practicality of using a blog in English writing class.  It means that blog as learning media is very influential in the development of students' learning process. The interview result also showed that online blogging provided many advantages such as being easy to operate, writing can be accessed by all readers in the world, receiving and giving comments on friends' blogs, no longer needing to the stationary, and encouraging the student's creativity to write systematically.